2018
DOI: 10.1186/s12939-018-0870-5
|View full text |Cite
|
Sign up to set email alerts
|

A survey of availability, price and affordability of essential medicines from 2011 to 2016 in Chinese secondary and tertiary hospitals

Abstract: BackgroundEssential medicines are those drugs that satisfy the priority health care needs of the population and help with functioning healthcare systems. Although many countries have formulated an essential medicine list, almost half of the global population still lack regular access to essential medicines. Research about the initiation of National Essential Medicines Policy in Chinese secondary and tertiary hospitals is inadequate, and the long-term effect on access after the reform is still unknown. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 20 publications
(16 reference statements)
1
30
0
Order By: Relevance
“…And when medicines are prescribed in PHCs, I have to go to a tertiary hospital to get them.” Therefore, national essential drug list should be expanded, and measures such as increasing the use of non-essential drugs at the grassroots level should be taken. Some cities have conducted pilot reforms, but the effect needs further verification [24, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…And when medicines are prescribed in PHCs, I have to go to a tertiary hospital to get them.” Therefore, national essential drug list should be expanded, and measures such as increasing the use of non-essential drugs at the grassroots level should be taken. Some cities have conducted pilot reforms, but the effect needs further verification [24, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in research conclusions may be due to the use of data from different regions, research period or study design. But overall, these findings have demonstrated that the NEMP interventions are effective: the availability of essential medicines had improved,56 57 but remains at a low level58 59 and had a problem of regional inequity60; drug prices were reduced significantly,57 61–63 and the affordability of essential medicines has improved57 59 60; and the rational use of medicine has effectively improved, but remained poor 56 64–67. In the subjective questionnaire surveys, patients were satisfied with the price and quality of essential medicines 68.…”
Section: Coverage Of Health Servicesmentioning
confidence: 96%
“…A standardized method was developed by the World Health Organization (WHO) and Health Action International (HAI) and has been used in Malaysia, China, Pakistan, Thailand, Sri Lanka, Ethiopia, India, Malawi, Haiti, etc. Most surveys focused on the essential medicines for adults [24,25,26,27,28] and children [29,30,31,32]. Some others focused on medicines for cardiovascular patients [33,34], antidiabetics [35,36], and orphans [37,38].…”
Section: Introductionmentioning
confidence: 99%